The Accuracy Of Task Completion In The Implementation Of PATEN : Ketepatan Penyelesaian Tugas Dalam Pelaksanaan Paten - Isyarah Rosana Amalia; Isna fitria Agustina (Academia Open, 2021)
This study aims to determine the accuracy of task completion in the implementation of PATEN in Candi District. This type of research is descriptive qualitative research. Data collection techniques were carried out by observation, interviews, documentation, and literature studies. Data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The results showed that the accuracy of the completion of tasks in the implementation of PATEN in Candi District, namely the completion of a PATEN application in the KTP service, could be completed within 7 days with a note that the file requirements were complete so that it could be processed immediately. In the management of ID cards, Candi Subdistrict employees have carried out their duties to the maximum. However, in terms of managing E-KTP, there are obstacles in terms of coordination with the Ministry of Home Affairs located in Jakarta where the server at the Ministry of Home Affairs is turned off every 3 hours for server maintenance purposes, then after that 5 minutes later it is turned on again. So this causes the processing of E-KTP takes a long time